Pathological Changes in Soft Tissue Associated with Impacted Third Molars - Anjum, Rabia; Naseem, Nadia; Usman, Mohammad; Nagi, A.H (International Journal of Pathology, 2018)
Objectives: To determine the pathological changes in soft tissues associated with impacted third molars.Study Design: Descriptive studySoft tissue specimens were taken from dental follicle or pericoronal tissue of 100 patients. Gross and microscopicfindings were noted.Results: Mean age of the patients was 27.58 years with male to female ratio being 1.2:1.Common clinical presentationswere pain (85%), limited mouth opening (25%), gingival redness and swelling (77%) pericoronitis (74%)and hard swelling in posterior region of mandible (4%). A total of 43% were completely while 57% were partiallybony impacted. On radiography, 59% mesioangular, 26% vertical, 9.0% horizontal and 6.0% distoangular impactionswere seen .Two patients presented with large radiolucent lesions.Microscopically, epithelial hyperplasia (62%), basal layer atypia (30%), surface ulceration (22%) and papillomatosis(15%) were seen. Connective tissue changes included inflammation (92%), hyalinization (62%), fibrinoidnecrosis (45%) and calcification (14%). Among inflammation 45%, 32 % and 15% biopsies showed mild, moderateand severe degree of inflammation respectively. Dentigerous cysts in 3% while 1% cases each of odontogenickeratocyst and plexiform variant of ameloblastoma was found.Conclusion: Impacted third molar is associated not only with inflammatory changes but also with cystic and neoplasticchanges.